Live-Streaming Adoption Strategies in Downstream-Dominant Supply Chain - Delong Jin (Mathematics)
In recent years, live streaming has become popular among merchants as it helps them obtain direct access to and attract customers. This study examines how weak upstream providers and strong downstream sellers adopt live streaming in a supply chain framework. It uses a theoretical game model with one provider and one seller. The seller sets the procurement price, and then the provider decides the supply level. Both can use live streaming alongside traditional channels. The results show that (1) live streaming raises both procurement and retail prices in traditional channels; (2) retail prices may differ or coincide between channels when different parties use live streaming; (3) as live streaming’s market cultivation efficiency decreases, the adoption strategies shift from both parties using it to only the provider or neither; and (4) live streaming always benefits the provider but harms the seller, with the overall impact on the supply chain depending on the cultivation efficiency and types of equilibrium strategies.